MANUAL OF PESTS AND NATURAL ENEMIES IN CEDAR ROJO DE TAMAULIPAS, NORTH OF VERACRUZ AND SAN LUIS POTOSÍ - Ruíz Cancino, Enrique (Libros UAT, 2018)
The tropical red cedar, Cedrella odorata Linnaeus, is a tree whose precious wood has high commercial value. For many years the wood of the native populations has been used, reason why commercial plantations have been established in several states of the country. In Mexico the pests of the red cedar had not been studied, except the honeydew borer, which affects the outbreaks, leading to the abandonment of the crop in areas of southeastern Mexico and Central America; the presence of termites and wood borers has been recorded only for some states in the southeast of the country. This research of the Academic Body "Applied Entomology" of the Autonomous University of Tamaulipas was carried out from 2000 to 2002. The plagues of the red cedar and its natural enemies were collected in Tamaulipas and in the northern zone of Veracruz and San Luis Potosí. The identification of the insects and mites obtained was made by Mexican specialists from the United States, England and Russia. Through this project it is now known that red cedar has a wide distribution in the state of Tamaulipas, being attacked by the meliáceas borer, the leafminer, two species of leafhoppers, the cedar milkweed, three species of scales, a mealy louse and by the spider of two spots. The natural enemies are mainly parasitic wasps of seven families; the predators include a species of catarinita and one of thrips that act like predators of the spider of two spots, whereas another catarinita and one brown laceworm predates to the mealy louse. The plagues, the natural enemies and their respective associations were new records for the Mexican Republic.